El arte como trabajo: Relectura del pensamiento de Chalena Vásquez - Magallanes Ortiz, Milagros E. (2025)
This article offers a contemporary rereading of the ideas of Chalena Vásquez, a renowned Peruvian musicologist, based on her work Teoría del arte y economía de la cultura: Los procesos de producción artística (1978/2019). It examines her conception of art as a complex productive process—symbolic, material, and social—in dialogue with positive organizational psychology and contemporary studies on creative collaboration. Through this interdisciplinary framework, the paper reflects on the structural challenges faced by the Peruvian cultural industries, characterized by labor precariousness, informality, and the concentration of opportunities in the Lima Metropolitan area. It argues that Vásquez’s theoretical approach, complemented by perspectives on well–being and cooperation, can inspire more equitable and sustainable cultural policies, fostering creative work environments grounded in resilience, solidarity, and social justice. Thus, culture is reaffirmed as a collective right and art as a space for social transformation.